Dichoptic training improves contrast sensitivity in adults with amblyopia. (September 2015) - Li, Jinrong; Spiegel, Daniel P.; Hess, Robert F.; Chen, Zidong; Chan, Lily Y.L.; Deng, Daming; Yu, Minbin; Thompson, Benjamin
Highlights: Dichoptic training improved contrast sensitivity in adults with amblyopia. The improvements exceeded test–retest variability for the contrast sensitivity task. Dichoptic training led to greater contrast sensitivity improvements than monocular training. Abstract: Dichoptic training is designed to promote binocular vision in patients with amblyopia. Initial studies have found that the training effects transfer to both binocular (stereopsis) and monocular (recognition acuity) visual functions. The aim of this study was to assess whether dichoptic training effects also transfer to contrast sensitivity (CS) in adults with amblyopia. We analyzed CS data from 30 adults who had taken part in one of two previous dichoptic training studies and assessed whether the changes in CS exceeded the 95% confidence intervals for change based on test–retest data from a separate group of observers with amblyopia. CS was measured using Gabor patches (0.5, 3 and 10 cpd) before and after 10 days of dichoptic training. Training was delivered using a dichoptic video game viewed through video goggles ( n = 15) or on an iPod touch equipped with a lenticular overlay screen ( n = 15). In the iPod touch study, training was combined with anodal transcranial direct current stimulation of the visual cortex. We found that dichoptic training significantly improved CS across all spatial frequencies tested for both groups. These results suggest that dichoptic training modifies the sensitivity of the neural systems that underpin monocular CS.